Theoretical Perspectives on Cooperative Learning - ., Yusnani (KnE Social Sciences, 2018)
Cooperative learning is an instructional method designed to encourage students to work together on academic tasks. In this study, the researcher focuses on the cooperative learning and cognitive developmental, behavioral and social interdependence, developing on Piagetian and Vygotskian theories. Cognitive interdependence is a mental state characterised by pluralism and collective representations of the self-in-relationship. Behavioral interdependence refers to the mutual impact that people have on each other as their lives and daily activities intertwine. Social interdependence relates to positive interdependence, individual accountability, promotive interaction, appropriate use of social skill, and group processing. This research demonstrates that cooperative learning enhances students' social interaction and maximizes their academic skills. Keywords: cognitive developmental, behavioral, social interdependence